(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Schizophrenia is a severe mental disorder characterized by positive, negative, and cognitive symptoms that affect the quality of life. Risperidone is widely known as second-generation antipsychotic that is effective to treat schizophrenia. Unlike the first-generation antipsychotic, risperidone has a lower impact on the extrapyramidal adverse effect. However, individually, the risperidone treatment response may be different caused by the genetic polymorphisms. This review aims to examine the association of genetic polymorphisms with risperidone treatment response in schizophrenia. Method: The review was conducted using the Pubmed database and 49 articles included in this review among 80 articles obtained in an initial search. The result showed genetic polymorphisms which affects risperidone therapy include DRD2, genetic polymorphisms on serotonin, cytochrome P450, BDNF, COMT, and ABCB1. Those polymorphisms might increase or decrease pharmacokinetics and pharmacodynamic profile of risperidone. In addition, genetic polymorphisms also contributed to the risk of metabolic syndrome and hyperprolactinemia induced by risperidone treatment. Conclusion: Based on those findings, several genetic polymorphisms had an association with therapeutic outcomes and side effect after risperidone treatment. Genetic polymorphisms screening may be useful for drug choices or dosage adjustment that safer and effective for patients.